The Gaza Strip: politics and environment - Shomar, Basem (Water policy, 2011)
In a region where politics is part of the vocabulary of daily life, this study reveals the environment as a victim of politics in the Gaza Strip. The environmental crisis in Gaza continues to worsen as the groundwater becomes increasingly polluted and the political situation delays hope of “resting” the Gaza aquifer and finding solutions for proper disposal of sewage and solid waste. Wastewater treatment plants (WWTPs) have been destroyed more than once as a result of the turbulent political situation. The Beit Lahia wastewater treatment plant flooded and killed several people in addition to causing casualties and displacing thousands of people, besides destroying homes and killing animals. The closure of the Gaza Strip led to a total paralysis of the economic sector. People's diets were seriously affected. The effects on the industrial sector were not limited only to economic dimensions but affected the environment as well. In mid-2007 alone, more than 70% of the industrial sector was closed and the environmental indicators showed around a 70% decrease in the industrial waste production compared to the previous six years. However, the pollution load was increasing due to the absence of technologies and wastewater treatment facilities. Despite all the complicated circumstances in the Gaza Strip, the population growth rate is the highest in the world which means more needs, further depletion of natural resources, and more waste and pollution.
Gesehen am 30.11.2022